Micropopulation mapping of the mouse parafascicular nucleus connections reveals diverse input–output motifs - Gonzalo-Martín, Enrique; Alonso-Martínez, Carmen; Sepúlveda, Lucía Prensa; Clasca, Francisco (Frontiers in Neuroanatomy, 2024)
In primates, including humans, the centromedian/parafascicular (CM-Pf) complex is a key thalamic node of the basal ganglia system. Deep brain stimulation in CM-Pf has been applied to for the treatment of motor disorders such as Parkinson’s disease or Tourette syndrome. Modeling in rodents the cellular mechanisms of these effects may thus offer relevant pathophysiological insights. However, the equivalence between the primate CM-Pf and the nucleus regarded as analogous in rodents (Parafascicular, Pf) remains unclear. Here, we analyzed the neurochemical architecture and brain-wide input-output motifs in the mouse Pf at micropopulation level with anterograde and retrograde labeling methods. Specifically, we mapped and quantified the sources of cortical and subcortical input to different Pf subregions, and mapped and compared the distribution and terminal structure of their axons. We found that projections to Pf arise predominantly (>75%) from the cerebral cortex, with an unusually strong (>45%) Layer 5b component, which, is in part, contralateral. The intermediate layers of the superior colliculus are the main subcortical input source. On its output side, Pf axons predominantly innervate the striatum. In much sparser fashion, they innervate other basal ganglia nuclei, including the subthalamic nucleus (STN), and the cerebral cortex. Differences are evident between the lateral and medial portions of Pf, both in chemoarchitecture and in connectivity. Lateral Pf axons innervate territories of the striatum, STN and cortex known to be involved in the sensorimotor control of different parts of the contralateral hemibody. In contrast, the mediodorsal portion of Pf innervates oculomotor-limbic territories of the above three structures. Our data thus indicate that the mouse Pf consists of several neurochemically and connectively distinct domains whose global organization bears a marked similarity to that described in the primate CM-Pf complex.